Coffee boom, government expenditure, and agricultural prices": the Colombian experience - Montes Llamas, Gabriel; García García, Jorge (International Food Policy Research Institute, 1988)
In this report, the authors examine the effects on agricultural incentives in Colombia of two influential economic forces: the coffee boom in the 1970s and rapidly expanding public sectors. In Colombia, the turbulence in trade and exchange rate regimes brought about by the coffee boom presents a classic example of the Dutch-disease phenomenon. In their analysis of government's expanding role as a demander of goods and services, the authors also examine the effects on farm output and on rural employment as they pertain to rural incomes and wage rates under the argument that government expenditure biased toward the nontraded sector discourages growth in agriculture and industry.